Pengaruh Remedial Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akuntansi Kelas XII Program IPS SMA Negeri 1 Takalar - Muhammad Anandy Anizar; M. Ridwan Tikolah; Samsinar Samsinar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the effect of remediation on student learning outcomes in the class XII accounting subject of the Social Sciences program at SMA Negeri 1 Takalar. The variables in this research are remedial as the independent variable and learning outcomes as the dependent variable. The population of this study was all students in class XII IPS 1 and XII IPS 2 at SMA Negeri 1 Takalar. The sampling technique uses a total sampling technique, samples from the population are obtained from the entire population with a sample of 62 students. The data collection techniques used are observation, questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing, and hypothesis testing. Based on the results of the data analysis that has been carried out, remedial descriptive statistical analysis results were obtained at 85.59 percent which is classified as very high and student learning outcomes were 89.35 percent which is classified as good. From the results of simple linear regression analysis, remedial Y=68.671 + 0.355X is obtained, which means that for every additional 1 remedial value, the learning outcome value increases by 0.355. Then the coefficient of determination value was obtained at 0.168 or 16 percent, which means that remedial contributed 16 percent to student learning outcomes and the remaining 84 percent was influenced by other factors. Meanwhile, from the results of the t-test analysis, a significant value of 0.000 <0.05 was obtained, which means that remedial has a positive and significant effect on learning outcomes, thus the hypothesis is accepted. This research aims to determine the effect of remediation on student learning outcomes in the class XII accounting subject of the Social Sciences program at SMA Negeri 1 Takalar. The variables in this research are remedial as the independent variable and learning outcomes as the dependent variable. The population of this study was all students in class XII IPS 1 and XII IPS 2 at SMA Negeri 1 Takalar. The sampling technique uses a total sampling technique, samples from the population are obtained from the entire population with a sample of 62 students. The data collection techniques used are observation, questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing, and hypothesis testing. Based on the results of the data analysis that has been carried out, remedial descriptive statistical analysis results were obtained at 85.59 percent which is classified as very high and student learning outcomes were 89.35 percent which is classified as good. From the results of simple linear regression analysis, remedial Y=68.671 + 0.355X is obtained, which means that for every additional 1 remedial value, the learning outcome value increases by 0.355. Then the coefficient of determination value was obtained at 0.168 or 16 percent, which means that remedial contributed 16 percent to student learning outcomes and the remaining 84 percent was influenced by other factors. Meanwhile, from the results of the t-test analysis, a significant value of 0.000 <0.05 was obtained, which means that remedial has a positive and significant effect on learning outcomes, thus the hypothesis is accepted.